Implementation Of Gagne's Nine Events On Islamic Education Subjects At Sdn Tamansari 03 Wuluhan Jember - Firda; Khoirul Anam (Kirana Publisher (KNPub), 2022)
Every learning theory has a focal point that takes center stage. There is more emphasis on the learning process, there is emphasis on the learning process, there is emphasis on the content or what is learned, there is more emphasis on the learning process, and there is emphasis on the learning process, there is emphasis on learning outcomes, there is emphasis on the content or what is learned, there is more emphasis on the learning process, and there is emphasis on themselves. We will continue to strive to provide the best solution for those of you who want to learn more.One of the important learning theories and principles to be applied or applied in learning activities is the theory of Robert M. Gagne is known for his 9 learning events or nine instructional events model. This research uses qualitative research with field research approach. Data collection techniques using insights, observations and document studies. The Data obtained were analyzed and tested the usefulness of using triangulation. The purpose of this study is to describe and analyze how the process of implementing Gagne nine events on Islamic education subjects at SDN Tamansari 03 Wuluhanjember. The results of this study indicate that the implementation of Gagne nine events in learning events include getting attention, informing learners of overall training objectives, stimulating recall of previous lrarning, presenting rhe stimulus/ content, providing tutoring, eliciting performance, providing feedback, assessing performance and enchancing retention and transfer. Keyword: Implementation, Gagne’s Nine Event, Islamic Education Subjects